(untitled) (Research, Society and Development, 2022)
The Covid-19 pandemic has shaken the public health system and the performance of several professionals in the fight against the spread of the virus. Objective: To analyze the feelings experienced by health professionals who work in public health services in the Brazilian Midwest in the face of Covid-19. Method: Cross-sectional, quantitative research, carried out between January/2021 and August/2021, through a structured online survey made available on social networks. Results: 79.9% of the population was female. As for the feelings experienced by professionals when reporting fear of contaminating the family, the following were evidenced: anguish 254 (95.5%), p < 0.001; sadness 249 (94.7%), p < 0.001; stress 259 (94.5%), p < 0.001 and anxiety 242 (94.9%), p < 0.001. With regard to psychological support, only 21.1% reported having been referred for follow-up by psychology professionals. Therefore, the importance of caring not only for the patient but also for the caregiver. Thus, it is necessary to provide assistance to health professionals through support networks in various regions.